2003
DOI: 10.1046/j.1462-5822.2003.00259.x
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of Actinobacillus actinomycetemcomitans outer membrane vesicles with HL60 cells does not require leukotoxin

Abstract: Summary Outer membrane derived vesicles (MVs) secreted by

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
70
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 56 publications
3
70
0
Order By: Relevance
“…Outer membrane vesicles (OMVs) released by this organism carry multiple proteins, and density gradient centrifugation supports the notion that there may be subpopulations of vesicles exhibiting slight variations in protein composition (7,19). Further to earlier reports revealing the OMV association of leukotoxin (LtxA) and a concomitant leukotoxic activity of A. actinomycetemcomitans OMVs (19,20), we have demonstrated that the OMVs could simultaneously deliver multiple proteins, including OmpA and biologically active cytolethal distending toxin (CDT), into HeLa cells and human gingival fibroblasts (HGF) (7). Hence, OMVs released by this species likely play a role in periodontal disease by delivering biologically active toxins and additional virulence factors into susceptible cells of the periodontium.…”
supporting
confidence: 73%
“…Outer membrane vesicles (OMVs) released by this organism carry multiple proteins, and density gradient centrifugation supports the notion that there may be subpopulations of vesicles exhibiting slight variations in protein composition (7,19). Further to earlier reports revealing the OMV association of leukotoxin (LtxA) and a concomitant leukotoxic activity of A. actinomycetemcomitans OMVs (19,20), we have demonstrated that the OMVs could simultaneously deliver multiple proteins, including OmpA and biologically active cytolethal distending toxin (CDT), into HeLa cells and human gingival fibroblasts (HGF) (7). Hence, OMVs released by this species likely play a role in periodontal disease by delivering biologically active toxins and additional virulence factors into susceptible cells of the periodontium.…”
supporting
confidence: 73%
“…In contrast, although leukotoxin is associated with the surface of A. actinomycetemcomitans OM vesicles, the toxin is not responsible for the adherence of the vesicles with HL60 human myeloid leukemia cells (Demuth et al 2003). After a brief, 2-min incubation, A. actinomycetemcomitans OM vesicle antigens are found around the periphery of the cells.…”
Section: Adherence and Entry Into Host Cells And Tissuesmentioning
confidence: 87%
“…While LtxA can be associated with the outer membrane (Ohta et al, 1991;Berthold et al, 1992;Johansson et al, 2000;Diaz et al, 2006), released within lipid vesicles (Kato et al, 2002;Demuth et al, 2003), and secreted from cells as soluble protein (Brogan et al, 1994;Kachlany et al, 2000), we believe that TdeA plays a role in all of these processes. Because RTX toxins are transported through the bacterial cell envelope without a periplasmic intermediate (Gray et al, 1986;Koronakis et al, 2004), LtxA would have to be exported through TdeA before localizing to the outer membrane or within vesicles.…”
Section: Discussionmentioning
confidence: 78%